Financial ratio analysis of financial distress in Indonesia stock exchange-listed customer goods corporations - Sutrismi, Sri; Rachman, Rosyidah; Rusman, Hedar; Khaddafi , Muammar; RoziqiFath, Zain Fuadi Muhammad (SEAN Institute, 2024)
The primary objective of this research is to assess the operational efficiency and financial well-IDXng of consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022 through the examination of financial ratios. Data for the research was acquired through a literature review that utilized four company samples derived from Indonesia Stock Exchange data. This research methodology obtains pertinent financial ratio data through a literature review. The outcomes demonstrated a favourable performance in general, as evidenced by ratio values including retained earnings to total assets, working capital to total assets, return on assets (ROA), and current ratio, which indicated favourable working capital management, asset optimisation, and ability to fulfil current obligations. The results presented in this study offer a positive outlook regarding the adaptability and stability of consumer products firms operating within the Indonesian capital market.